The nature of corporate social responsibility disclosure and investment efficiency: Evidence from China - Huang, Fangliang; Chen, Meng; Liu, Rongbing (Frontiers in Environmental Science, 2023)
Corporate social responsibility (CSR) disclosure has gained more attention from both practitioners and scholars. Company executives are starting to seek competitive differentiation from their sustainability strategies (McKinsey & Company, 2020). This study explores the link between CSR disclosure and investment efficiency using a sample of Chinese-listed firms from 2010 to 2019. The findings suggest that CSR disclosure improves investment efficiency through reducing information asymmetry and agency cost. Also, mandatory CSR disclosure has a more significant effect on investment efficiency than voluntary CSR disclosure. In addition, this study finds that the nature of ownership (state-owned vs. non-state-owned), CSR performance, institutional ownership, and the level of industry competition all affect this relationship. The study provides meaningful implications for future CSR disclosure policy development.